NURTURING CREATIVITY THROUGH THE REGGIO EMILIA APPROACH: A STUDY OF EARLY LEARNING PRACTICES IN MALAYSIAN TASKA - TUAN ELISYA MAISARAH TUAN SOUPI; MOHD NAZRI ABDUL RAHMAN (Proceeding International Symposium on Global Educatiorg Psychology, and Cultural Synergy, 2025)
Fostering Creativity via the Reggio Emilia Approach: An Examination of Early Learning Practices in Malaysian TASKA. This article examines the application of the Reggio Emilia Approach in Malaysian Taman Asuhan Kanak-Kanak (TASKA) and its significance in fostering creativity and comprehensive development in young children. The Reggio Emilia philosophy, originating in Italy, perceives children as competent, curious, and capable learners who articulate themselves through many kinds of communication, commonly termed the "hundred languages." This study used a qualitative research design, incorporating a literature review, interviews with TASKA educators, and document analysis to investigate the application of Reggio concepts in Malaysian early childhood settings. Research indicates that Reggio-inspired TASKA centres prioritise creativity via project-based learning, child-centered surroundings, collaborative instruction, and active parental engagement. Educators serve as facilitators who monitor and direct learning, whereas documentation methods promote reflection and foster connections between the school and home. Notwithstanding problems such restricted training and budget limitations, the methodology has demonstrated considerable beneficial impacts on children's curiosity, confidence, and problem-solving skills. The study indicates that the Reggio Emilia concept possesses significant potential to revolutionise early education in Malaysia by fostering reflective teaching, creativity, and culturally pertinent learning methods.